2014
DOI: 10.1186/1752-4458-8-16
|View full text |Cite
|
Sign up to set email alerts
|

An overview of Ghana’s mental health system: results from an assessment using the World Health Organization’s Assessment Instrument for Mental Health Systems (WHO-AIMS)

Abstract: BackgroundThis survey provides data on the Mental Health System in Ghana for the year 2011. It supplies essential planning information for the implementation of Ghana’s new Mental Health Act 846 of 2012, a renewal of the Ghana 5 year plan for mental health and it contributes to international knowledge base on mental health. It provides a baseline from which to measure future progress in Ghana and comparison data for use in other countries. In addition to reporting our findings we describe and analyse deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(193 citation statements)
references
References 2 publications
2
189
1
1
Order By: Relevance
“…La proporción de establecimientos de atención primaria que alcanzó esta meta fue de 57% en Uganda (24) , 40% en Ghana (25) y entre 21 y 50% en México (26) . Considerando los establecimientos de todo nivel, McBain et al encontraron una tasa de 71% en una muestra de 63 países de bajos o medianos ingresos (27) .…”
Section: Discussionunclassified
“…La proporción de establecimientos de atención primaria que alcanzó esta meta fue de 57% en Uganda (24) , 40% en Ghana (25) y entre 21 y 50% en México (26) . Considerando los establecimientos de todo nivel, McBain et al encontraron una tasa de 71% en una muestra de 63 países de bajos o medianos ingresos (27) .…”
Section: Discussionunclassified
“…In particular, legislation and policies, which have a sustainable impact on consumers of services, have historically received little priority. Until 2011, the mental health services had relied on an outdated mental health policy of 1994 and a revised mental health strategic plan . Similarly, until 2012, when the Mental Health Act 2012 (Act 846) was enacted, mental health services have functioned on the outdated Mental Health Legislation of 1972 (Draft, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is the need for proper training and recruitment of psychiatric and other mental health personnel, such as doctors, nurses, and social workers and in addition to increased funding for mental health services to augment the challenges of inhuman treatment, stigma, and discrimination associated with mental illness in the country (Roberts et al 2014).…”
Section: Recommendationsmentioning
confidence: 99%
“…A previous 2008 study revealed that Ghana had ten psychiatrists compared to 13,074 physicians (Doku et al 2012). The annual budget allotted to mental health is 1.4% of the health budget (Roberts et al 2014) compared to 10% or more of national health budgets allotted to mental health in the Western world (Lurie 2014).…”
Section: Mental Health In Ghanamentioning
confidence: 99%
See 1 more Smart Citation